Original Research: Descriptive or Analytical, Either-Or or Both-And? - José Florencio Lapeña (Philippine Journal of Otolaryngology Head and Neck Surgery)
descriptive (adj.) “serving or aiming to describe,” 1751, from Late Latin descriptivus, from descript-, past-participle stem of describere “to write down, copy; sketch, represent,” from de “down” (see de-) + scribere “to write” (from PIE root *skribh- “to cut”). Related: Descriptively; descriptiveness.